Epidemiology and susceptibility of pathogens from SMART 2011-12 Turkey: evaluation of hospital-acquired versus community-acquired urinary tract infections and ICU- versus non-ICU-associated intra-abdominal infections - DURMUŞOĞLU, LÜTFİYE; KORTEN, VOLKAN (OXFORD UNIV PRESS, 2017)
Objectives: To describe the epidemiology and susceptibility of pathogens (including ESBL producers) from hospital-acquired (HA) versus community-acquired (CA) urinary tract infections (UTIs) and ICU-versus non-ICU-associated intra-abdominal infections (IAIs) in Turkey as a part of the SMART study. Methods: For this report, Gram-negative pathogens (363 from UTIs and 458 from IAIs) were collected in 2011 and 2012 at six hospitals in Turkey. HA versus CA UTIs and ICU-versus non-ICU-associated IAIs were compared for the species isolated, percentage of ESBL-positive isolates by species and susceptibility for overall and individual Gram-negative species. Results: Escherichia coli was the most common pathogen identified in HA (40.2%) and CA (73.9%) UTIs and ICU-associated (25.8%) and non-ICU-associated (43.3%) IAIs. The rate of ESBL-positive E. coli was significantly higher in HA than in CA UTIs (50.5% versus 38.2%, P < 0.001) and in non-ICU-associated than in ICU-associated IAIs (52.5% versus 29.2%, P = 0.029). Of the drugs studied, only amikacin was active against >= 90% of pathogens in UTIs, while ertapenem, imipenem and amikacin were active against >= 90% of E. coli; and imipenem, amikacin and cefoxitin were active against >= 90% of Klebsiella pneumoniae in IAIs. Conclusions: Our findings demonstrated that E. coli continues to be the principal pathogen of UTIs and IAIs in Turkey. Along with a high rate of ESBL-positive isolates, high antimicrobial resistance among Gram-negative bacilli from either UTIs or IAIs was noted particularly in the case of HA UTIs and ICU-associated IAIs, with a higher likelihood of carbapenem-or amikacin-based therapy to provide the broadest activity against bacterial pathogens.
Keywords: GRAM-NEGATIVE BACILLI; IN-VITRO SUSCEPTIBILITIES; RESISTANCE TRENDS SMART; ASIA-PACIFIC REGION; ANTIMICROBIAL RESISTANCE; CHILDREN GUIDELINES; DISEASES SOCIETY; EASTERN-EUROPE; UNITED-STATES; SURVEILLANCE